Pelaksanaan Program PKM-KKN Kampus Peduli Stunting di Kelurahan Rangkapan Jaya Baru, Depok. - Winda Nidya Putri Fitriana; Mustika Dewi Muttaqien; Ika Rahayu Satyaninrum; Hartin Kurniawati; Isep Djuanda; Taufik Hidayatulloh; Ernawati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Children's growth and development is influenced by several factors, including nutrition and nutrition. Stunting in early childhood will reduce the quality of growth and development as well as children's intelligence, so it is very important for various parties in society and academic circles to take a role in reducing stunting rates in the environment where they live. This community service aims to provide healthy food menus with balanced nutrition as an effort to fulfill nutritional requirements for children under five who suffer from stunting in the Rangkapan Jaya Baru Village environment. The service method used is the Community Based Research (CBR) method which includes four stages, including laying the foundation, planning, collecting and analyzing data (information gathering and analysis) and acting on findings. The results of the service show that providing a healthy, nutritious menu directly for stunted children can be an innovation for Ocan Bananas and parents in providing adequate nutrition for children with an appearance and food preparation that is attractive to young children.